PENERAPAN ALGORITMA C4.5 UNTUK PREDIKSI TINGKAT KOMPETENSI KARYAWAN PT MULTISTRADA ARAH SARANA - Wahyono Wahyono; Agung Nugroho (Universitas Islam Lamongan, 2018)
The success of an organization or company is influenced by the competence of human resources in it in carrying out its duties. Assessment of competence in the company is very important because it is necessary to determine the level of competence of employees. So far, the competency level assessment is still done manually by providing certain criteria by the Personnel Department (HRD). The number of criteria and employees employed is quite difficult in the assessment of employee competency. In addition, the quality of employee work is also often changing. This is very influential on the future prospects of the company. The purpose of this study is to analyze and know the pattern of employee competency level. The research method used is Decission Tree Learning (DCT). The C4.5 algorithm is part of DCT. Algorithm C4.5, the data mining technique to create a decision tree that represents rules or rules. Of the 257 overall employee data is divided into two partitions, 80% for training data and 20% data testing. The result of application of algorithm C4.5 got its accuracy 80,39% with calculation of RapidMiner 5.3. This research produces a pattern of competency level that can be used by PT Multistrada Arah Sarana for employee monitoring process to determine whether or not to need training or promotion promotion